Numerical Simulation on Combustor of Impinging Stream Vortex Engine (ISVE). (August 2019) - Yu, Xiaojing; Liu, Yang; Pei, Jingqiu
Abstract: The impinging stream vortex engine (ISVE), with the advantages of strong thermal protection performance, low cost and simple structure, emerges as the times require. In this paper, the propellant mixing performance, atomization performance, combustion performance and thermal protection performance under different working conditions are calculated and analyzed by numerical simulation for the designed impinging swirl cooling thrust chamber, and the influence of thrust chamber structure on its flow and combustion performance is discussed. The results show that the wall temperature of the thrust chamber is lower than 400K, and the combustion efficiency reaches 93%. The double eddy current structure will strengthen the combustion reaction and make the top temperature of the thrust chamber too high, which will provide theoretical guidance for the next structural design of the thrust chamber.